Optimalisasi Ketrampilan Guru dalam Mengembangkan dan Memanfaatkan Taman Sejarah Berbasis Virtual Reality sebagai Media Pembelajaran Sejarah - Ba’in Ba’in; Eka Yudha Wibowo; Ibnu Sodiq; Santi Muji Utami; Faniska Handayani; Syakila Aulia Zandini (LP3M INSTITUT KH YAZID KARIMULLAH, 2024)
The targets of this service activity are high school/MA history teachers in Pati Regency. Based on initial observations with the head of the MGMP and several history teachers in Pati Regency, it can be concluded that these history teachers are deemed to need training and assistance regarding the development of innovative history teaching media in accordance with the demands of the Independent Curriculum, including the development of virtual reality-based history park media. This training activity is targeted to be attended by around 33 SMA/MA teachers who are members of the Pati Regency history MGMP. The strategies and steps that we hope can be implemented in this training activity include (a) Initial observations with brainstorming, experiences, obstacles and ideas regarding the implementation of the Merdeka Curriculum, especially regarding the development of learning media by utilizing 4G technology in history learning with MGMP administrators and teachers history of high school in Pati Regency. This training and mentoring activity was carried out at the same time as MGMP activities in July 2024. In the training activity, a presentation was made about the meaning of virtual reality-based historical parks, the use of virtual reality-based historical parks as an innovative history learning medium, and steps for developing virtual-based historical parks. reality. During the training activities, technical guidance and practice were also provided in the use of virtual reality-based historical parks as a medium for historical learning. After training and technical guidance, it continues with assistance to participants in implementing the training results. This mentoring activity was centered at 2 training partner schools with each being visited 3 times. The first visit provides practical assistance in implementing the training results, then continues with joint reflection as input for the second practice and so on until the third assistance. In the third mentoring, it is hoped that all participants will be used to applying the results of the training while encouraging students to produce work to strengthen students' literacy skills. The final activity was an evaluation by both the service team and the Pati Regency history MGMP. By taking this activity seriously, history teachers can develop and utilize virtual reality-based history gardens as an innovative history learning medium. The expected results are the growth of teacher and student creativity and increased student motivation and historical awareness. The service outputs that have been determined are: publications in national journals, news on electronic mass media, video highlights of activities uploaded to YouTube and HAKI.